Public administration and the constitution a conflict in world views. - Spicer, Michael W. (1994)
This paper examines the world views underlying public administration and the Constitution. The article presents two rather different ways of looking at the world, which are used as a framework to contrast the literature in public administration with the writings of the Founders. It is argued that whereas public administration is rooted in a world view that stresses the powers of reason, the world view underlying the Constitution stresses the limits of reason. This conflict in world views, which has not been fully appreciated in the literature, makes clear the problem of grounding public administration in the Constitution. The paper also presents an alternative approach to legitimating public administratio n, which is more consistent with the world view of the Founders. - Reproduced
Keywords: Public administration